Clinical outcomes in Caucasian patients with polypoidal choroidal vasculopathy. (November 2018) - Agorogiannis, Eleftherios; Pearce, Ian; Yadav, Sohraab; Parry, David; Beare, Nicholas
Abstract Purpose To describe treatment outcomes in a cohort of Caucasian patients with polypoidal choroidal vasculopathy (PCV). Methods Clinical charts from 48 eyes of 45 Caucasian patients with PCV were retrospectively reviewed. All cases were diagnosed with indocyanine green angiography. Best corrected visual acuity (BCVA) and optical coherence tomography (OCT) imaging were analyzed at baseline and final follow-up. Results Eyes were treated with a combination of verteporfin photodynamic therapy (PDT) and anti-vascular endothelial growth factor (VEGF) (n = 24), or PDT monotherapy (n = 9), or anti-VEGF monotherapy (n = 8), or no treatment (n = 7). Aflibercept was the anti-VEGF agent in 30 out of 32 eyes. Sixteen out of 24 eyes in the combination treatment group received initial PDT at diagnosis. All treatments led to stabilization of BCVA at final visit with a trend for better visual acuity in the anti-VEGF monotherapy group. There was a substantial reduction in central retinal thickness associated with resolution of subfoveal fluid and improvement in retinal pigment epithelial detachment in all treatment groups. BCVA and OCT findings remained stable in eyes which received no treatment. The use of PDT was associated with 0.5 fewer intravitreal injections per annum, which was not statistically significant. Conclusions In the largest series of Caucasian patients with PCV presented to date, anti-VEGF monotherapy, PDT, or their combination preserved visual acuity and improved subfoveal exudative changes. Combination treatment was not superior to anti-VEGF monotherapy.